Synthesis and Fluorescent Properties of Coumarin–Chalcone Hybrids. (September 2017) - Yang, Fang; Fan, Hongli; Xue, Ziyan; Wang, Xiaolong
Four coumarin–chalcone hybrids were synthesised utilising condensation of acetylcoumarin with three benzaldehydes and cinnamaldehyde, respectively. Moreover, the absorption and fluorescence spectra of these synthesised compounds in dichloromethane were measured.